Relationship between FVC, FEV1, FEV1/FVC% and serum lead level of the traffic policemen in Dhaka city. - Ahmed, Shahriar; Akter, Qazi Shamima; Ahmed, Rumana; Choudhury, Tasrina Rabia; Kabir, Farhana; Azim, Sabrina Fahmida (Journal of Bangladesh Society of Physiologist, 2018)
Background: Air pollution is increasing day by day in Dhaka city due to automobile exhaust emitted from huge number of vehicles. Automobile pollutants inhalation would increase the blood lead level which may be associated with acute and chronic respiratory disease. Objective: To observe the relationship of FVC, FEV1, FEV1/FVC% with serum lead level in traffic policemen in Dhaka city. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College (DMC),Dhaka from July 2014 to June 2015. The study group enrolled 50 apparently healthy traffic policemen aged 25 to 45 years engaged in traffic control at different traffic junctions of Dhaka city and the control group consisted of apparently healthy subjects working in bank and different offices in Dhaka city with similar BMI and age to traffic police subjects. FVC, FEV1 and FEV1/FVC% of all the subjects were measured by digital spirometer and serum lead level was estimated by Flame Atomic Absorption Spectrophotometry. Statistical analysis was done by Pearson’s correlation coefficient test. Independent sample ‘t’ test. Results: In this study, serum lead level was found significantly higher in the traffic policemen than the control group. FVC, FEV1 and FEV1/FVC showed negative correlation with serum Lead level but it was not statistically significant. Conclusion: From the result of this study, it can be concluded that traffic policemen may be in greater exposure to severe air pollution with higher lead content in Dhaka city and it may affect their lung function. J Bangladesh Soc Physiol. 2018, June; 13(1): 13-16